A Magnetically Separable Pd Single‐Atom Catalyst for Efficient Selective Hydrogenation of Phenylacetylene. Issue 20 (15th April 2022) - Zhao, Linmin; Qin, Xuetao; Zhang, Xirui; Cai, Xiangbin; Huang, Fei; Jia, Zhimin; Diao, Jiangyong; Xiao, Dequan; Jiang, Zheng; Lu, Ruifeng; Wang, Ning; Liu, Hongyang; et al.
Abstract: Selective hydrogenation of alkynes to alkenes plays a crucial role in the synthesis of fine chemicals. However, how to achieve high selectivity and effective separation of the catalyst and substrate while obtaining high activity is the key for this reaction. In this work, a Pd single‐atom catalyst is anchored to the shell of magnetic core–shell particles that consist of a Ni‐nanoparticles core and a graphene sheets shell (Ni@G) for semi‐hydrogenation of phenylacetylene, delivering 93% selectivity to styrene at full conversion with a robust turnover frequency of 7074 h −1 under mild reaction conditions (303 K, 2 bar H2 ). Moreover, the catalyst can be recovered promptly from the liquid phase due to its magnetic separability, which makes it present good stability for enduring five cycles. Experimental and theoretical investigations reveal that H2 and substrates are activated by atomically dispersed Pd atoms and Ni@G hybrid support, respectively. The hydrogenation reaction occurs on the surface of Ni@G via hydrogen spillover from the metal to the support. Such a strategy opens an avenue for designing highly active, selective, and magnetically recyclable catalysts for selective hydrogenation in liquid reaction systems. Abstract : A magnetically separable single‐atom catalyst, Pd1 /Ni@G, is fabricated via anchoring atomically dispersed Pd single atoms on the shell of magnetic core–shell particles that consist of a Ni‐nanoparticles core and a graphene sheets shell (Ni@G). The obtained Pd1 /Ni@G catalyst displays robust catalytic performance for selective hydrogenation of phenylacetylene with efficient activity and selectivity, as well as good stability, and it can be promptly recycled from the liquid reaction systems due to its magnetic separability.